2021
DOI: 10.3390/cells10123406
|View full text |Cite
|
Sign up to set email alerts
|

Maresin-1 Prevents Liver Fibrosis by Targeting Nrf2 and NF-κB, Reducing Oxidative Stress and Inflammation

Abstract: Liver fibrosis is a complex process characterized by the excessive accumulation of extracellular matrix (ECM) and an alteration in liver architecture, as a result of most types of chronic liver diseases such as cirrhosis, hepatocellular carcinoma (HCC) and liver failure. Maresin-1 (MaR1) is derivative of ω-3 docosahexaenoic acid (DHA), which has been shown to have pro-resolutive and anti-inflammatory effects. We tested the hypothesis that the application of MaR1 could prevent the development of fibrosis in an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(23 citation statements)
references
References 88 publications
1
18
0
Order By: Relevance
“…Previous studies indicated that activated microglia can damage neurogenesis and are mainly associated with cognitive and mood dysfunctions [ 41 ]. Maresin1 (MaR1), a newly identified metabolite of 22-carbon hexaenoic acid (DHA) derived from macrophages, displays anti-inflammatory and pro-inflammatory effects [ 42 ]. Notably, MaR1 has been demonstrated to significantly inhibit macrophage infiltration and inflammation in the hippocampus.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies indicated that activated microglia can damage neurogenesis and are mainly associated with cognitive and mood dysfunctions [ 41 ]. Maresin1 (MaR1), a newly identified metabolite of 22-carbon hexaenoic acid (DHA) derived from macrophages, displays anti-inflammatory and pro-inflammatory effects [ 42 ]. Notably, MaR1 has been demonstrated to significantly inhibit macrophage infiltration and inflammation in the hippocampus.…”
Section: Discussionmentioning
confidence: 99%
“…In cultured hepatocytes, RvD1 also inhibits hepatocyte proliferation and is implicated in attenuating cancer growth ( Lu et al, 2018b ). Consistently, both RvD and RvE prevent the progression to cancer ( Kuang et al, 2016 ; Rodriguez et al, 2020 ) and MaR treatment mitigated fibrosis induced by DEN ( Rodriguez et al, 2021 ). Again, the AKT-mTOR regulated autophagy in HSC contributes to the RvD inhibited fibrosis ( Li et al, 2021 ).…”
Section: Biological Functions Of Oxylipins In Liver Disease and Cance...mentioning
confidence: 72%
“…Furthermore, DEN administration results in excessive deposition of ECM protein (collagen) in rat liver and seems appropriate to study early events associated with the development of liver fibrosis (45). Some studies induced liver fibrosis by intraperitoneal injection of DEN in rats once a week for 4-6 weeks (46,47). DEN, a known carcinogen that leads to significant oxidative stress and DNA mutations, enhances lipotoxicity and accelerates the progression of fibrosis and cirrhosis, has long been used in hepatocellular carcinoma (HCC) models (48).…”
Section: Den-induced Liver Fibrosis Modelmentioning
confidence: 99%